Genetic variation in N- and C-terminal regions of bovine DNAJA1 heat shock protein gene in African, Asian and American cattle - Ajayi, Oyeyemi O. (J Genomics, 2018)
DNAJA1 or heat shock protein 40 (Hsp40) is associated with heat adaptation in various organisms. We amplified and sequenced a total of 1,142 bp of bovine Hsp40 gene representing the critical N-terminal (NTR) and C-terminal (CTR) regions in representative samples of African, Asian and American cattle breeds. Eleven and 9 different haplotypes were observed in the NTR in Asian and African breeds respectively while in American Brangus, only two mutations were observed resulting in two haplotypes. The CTR appears to be highly conserved between cattle and yak. In-silico functional analysis with PANTHER predicted putative deleterious functional impact of c.161 T>A; p. V54Q while alignment of bovine and human NTR-J domains revealed that p.Q19H, p.E20Q and p. E21X mutations occurred in helix 2 and p.V54Q missense mutation occurred in helix 3 respectively. The 124 bp insertion found in the yak DNAJA1 ortholog may have significant functional relevance warranting further investigation. Our results suggest that these genetic differences may be concomitant with population genetic history and possible functional consequences for climate adaptation in bovidae.